Gastroesophageal reflux symptoms and sleep quality among medical students at a private university in Lima, Peru: A cross-sectional study - Alvaro F. Montalvo-Peralta; Yolanda Abigail Miranda-Sagastegui; Frank J. Tinco-Pumacahua; David R. Soriano-Moreno (PLoS ONE, 2026)
Introduction Poor sleep quality is common among medical students and is associated with academic and health-related consequences. Gastroesophageal reflux disease (GERD) may contribute to sleep disturbances through biological and behavioral mechanisms, however, evidence in medical students is limited and previous studies have not adequately controlled for confounding. Objective To evaluate the association between GERD and sleep quality among medical students in Lima, Peru. Methods Cross-sectional analytical study conducted among medical students from a private university in Lima, Peru. Sleep quality was assessed using the Pittsburgh Sleep Quality Index, and GERD symptoms were measured with the Frequency Scale for the Symptoms of GERD. Poisson regression with robust variance was used to estimate adjusted prevalence ratios (aPR) with 95% confidence intervals (95% CI). Results A total of 171 students were analyzed (median age: 22 years; 64.9% female). The prevalence of GERD symptom burden was 76.6%, and poor sleep quality was observed in 84.8% of participants. Students with GERD symptom burden had a higher prevalence of poor sleep quality compared to those without GERD (aPR: 1.27; 95% CI: 1.03 to 1.58). Additionally, for each one-point increase in the GERD symptom score, the prevalence of poor sleep quality increased by 1.0% (aPR: 1.01; 95% CI: 1.003 to 1.018), demonstrating a dose–response relationship. Conclusion GERD symptoms were significantly associated with poor sleep quality among Peruvian medical students. This study provides context-specific adjusted evidence from an understudied Latin American medical student population. These findings support the need for screening strategies and early interventions targeting both conditions in this population.